Edwina, the dinosaur who didn't know she was extinct - Willems, Mo (Hyperion Books for Children, 2006)
Everyone in town loves Edwina the dinosaur except one little boy who is determined to prove to everyone, including Edwina, that dinosaurs are extinct.